Taxing the digital economy : theory, policy and practice - Elliffe, Craig, 1961- (New York: Cambridge University Press, 2021)
"In 2018, the total global e-commerce market worth roughly USD 7.7 trillion. Despite the size of this economy and its extraordinary growth rate, many multinational companies paid little tax in the countries in which they did business. This is not a problem that can be ignored. Digital companies grow much faster than other firms. In 2006, technology companies accounted for 7% of the top 20 market capitalisation of EU companies, by 2017 this had grown to 54%. Digital companies rely less on physical presence utilising intellectual property, enabling companies to set up a business far away from their consumers, where some of the actual economic activity takes place. Most concerning is the fact that, on average, digitalised businesses face an effective tax rate of only 9.5% compared to 23.2% for traditional business models.1 Consequently, there is widespread concern from governments and the public about the low level of income tax paid by companies operating in the digital economy"--
Includes bibliographical references and index.
Keywords: Corporations -- Taxation -- European Union countries -- Data processing; Electronic commerce -- Taxation -- Law and legislation -- European Union countries; Corporations -- Taxation -- Law and legislation -- European Union countries; Information technology -- Economic aspects -- European Union countries